(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2019)
The research was conducted in a Pardo ócrico sin carbonato soil without developed on igneous rocks in the CCS Frank País municipality Majibacoa, Las Tunas in the months of February and March 2016 with the objective of evaluating the effect of one stimulators of plant growth (Fitomas E) and biofertilizer EcoMic in morphological and productive variables in lettuce (Lactuca sativa, L.) cultivar Black Seeded Simpson. Was utilized an experimental design of blocks at random with eight treatments and four replies. The examined variables matched: height of the plant, length of the root, diameter of the stem, number of leaf for plants, mass of the plant and yield (kg m-2). A double classification variance analysis was performed with the Infostat statistical package, version 2016.The cultivation of the lettuce responded positively to the stimulators of the vegetable growth application and to the EcoMic in all the evaluated variables. The bigger performances, minor costs for weights and bigger profits got with the independent use from EcoMic and EcoMic combination themselves FitoMas E. The use of these alternatives is recommended to contribute to sustainable crop production.